Effect of the Mendelsohn maneuver and swallowing training in patients with senile vascular dementia complicated with dysphagia. Issue 5 (May 2021) - Zhang, Jianrong; Wu, Yu'e; Huang, Yanfang; Zhang, Shuqing; Xu, Liuqin; Huang, Xiaoyun; Wang, Xingshui; Huang, Qingping
Objective: We investigated the effect of the Mendelsohn maneuver and swallowing training in patients with senile vascular dementia complicated with dysphagia. Methods: We randomly classified 214 patients with senile vascular dementia and swallowing dysfunction into a control group (CG, n = 106) and observation group (OG, n = 108). Both groups underwent health education, psychological intervention, and training of the oral muscle group. The OG additionally underwent the Mendelsohn maneuver and swallowing training. The Hasegawa Dementia Scale (HDS), China Stroke Scale (CSS), and Neurobehavioral Cognitive Status Examination (NCSE) were used to evaluate dementia, neurological impairment, and cognitive dysfunction, respectively. Results: The OG had a higher rate of effective therapy than the CG. After intervention, the OG showed better swallowing function than the CG. At 15 days and 1 month after intervention, the OG had higher video fluoroscopic swallowing exam scores than the CG. The OG had lower serum interleukin (IL)-1, IL-6, and tumor necrosis factor-α levels than the CG. After intervention, the OG had higher HDS and NCSE scores and lower CSS scores than the CG. Conclusions: The Mendelsohn maneuver and swallowing training can improve swallowing function in patients with senile vascular dementia complicated with dysphagia and help to ameliorate the inflammatory response.